Sexual harassment in Antarctica : a study of five states parties - Victoria Grace Patenaude 1995- (2024)
Ritgerðin er lokuð til 15.04.2026 Sexual harassment on Antarctic stations is a pervasive issue that is further complicated by the unique challenges of the work environment, such as the lack of State sovereignty over the continent. The primary objective of this thesis is to determine how thorough the Polar Codes of Conduct of five Antarctic States Parties are toward tackling the numerous complexities of sexual harassment in Antarctica. To answer this I investigated the issue through two disciplines, social science and law. Using mainly academic literature and news articles I examined the history of the Antarctic workforce integrating women and the ongoing culture of harassment. This social science side of the thesis provides a background to the sexual harassment on Antarctic stations and identified key issues that enable the harassment or make it difficult to properly address. The thesis also uses an overview of relevant international laws and national laws for the five States. This addressed the sub-question ‘what are State’s obligations to protect women from sexual harassment and abuse in the Antarctic?’ The social science and law overviews supported the criteria selected for the analysis of the Polar Codes of Conduct. These all covered most of the selected criteria with different strengths between the five States. This was just an initial analysis that did not measure how well the Polar Codes of Conduct addressed the criteria, only if they addressed the subjects at all. Further time and resources would enable a more thorough analysis and expand to more States.